Evaluation of mobile microwave radiation severity at al-door residential complex in Iraq - Younes S. Alwan; Mohammad Sami Zidan; Mohammed Qasim Taha (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, the electromagnetic radiation of the mobile microwave signals, propagated by the mobile towers in Al-Door Residential Complex west of Iraq, is measured and evaluated. This complex contains main nodes and hub repeaters and feeders to transmit the service to the whole Salahuddin and the northern provinces. Therefore, this paper focused on this area to assess the radiation and to assess the radiation whether it is safe for humans or exceeded the dangerous level. The area has been divided on to 19 locations where there are mobile towers and the radiation is measured in these locations. The electric field intensity is unsafe and should be improved since it exceeds the level of 1.7 V/m. However, the magnetic field intensity is acceptable according to the measurements. In general, the electromagnetic radiation density is unsafe since many readings override the level of 1.3 μW/〖cm〗^2. The standards of the radiation severity are based on the recommendations of LATNEX Corp.